## RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations MCQS

These Solutions are part of RD Sharma Class 10 Solutions. Here we have given RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations MCQS

**Other Exercises**

- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.1
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.2
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.3
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.4
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.5
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.6
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.7
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.8
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.9
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.10
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.11
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.12
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations Ex 4.13
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations VSAQS
- RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations MCQS

**Mark the correct alternative in each of the following :**

**Question 1.**

If the equation x² + 4x + k = 0 has real and distinct roots, then

(a) k < 4

(b) k > 4

(c) k ≥ 4

(d) k ≤ 4

**Solution:**

**(a)** In the equation x² + 4x + k = 0

a = 1, b = 4, c = k

D = b² – 4ac = (4)² – 4 x 1 x k = 16 – 4k

Roots are real and distinct

D > 0

=> 16 – 4k > 0

=> 16 > 4k

=> 4 > k

=> k < 4

**Question 2.**

If the equation x² – ax + 1 = 0 has two distinct roots, then

(a) |a| = 2

(b) |a| < 2

(c) |a| > 2

(d) None of these

**Solution:**

**(c)** In the equation x² – ax + 1 = 0

a = 1, b = – a, c = 1

D = b² – 4ac = (-a)² – 4 x 1 x 1 = a² – 4

Roots are distinct

D > 0

=> a² – 4 > 0

=> a² > 4

=> a² > (2)²

=> |a| > 2

**Question 3.**

If the equation 9x^{2} + 6kx + 4 = 0, has equal roots, then the roots are both equal to

(a) ±

(b) ±

(c) 0

(d) ± 3

**Solution:**

**(a)**

**Question 4.**

If ax^{2} + bx + c = 0 has equal roots, then c =

**Solution:**

**(d)** In the equation ax^{2} + bx + c = 0

D = b^{2} – 4ac

Roots are equal

D = 0 => b^{2} – 4ac = 0

=> 4ac = b^{2}

=> c =

**Question 5.**

If the equation ax^{2} + 2x + a = 0 has two distinct roots, if

(a) a = ±1

(b) a = 0

(c) a = 0, 1

(d) a = -1, 0

**Solution:**

**(a)** In the equation ax^{2} + 2x + a = 0

D = b^{2} – 4ac = (2)^{2} – 4 x a x a = 4 – 4a^{2}

Roots are real and equal

D = 0

=> 4 – 4a^{2} = 0

=> 4 = 4a^{2}

=> 1 = a^{2}

=> a^{2} = 1

=> a^{2} = (±1)^{2}

=> a = ±1

**Question 6.**

The positive value of k for which the equation x^{2} + kx + 64 = 0 and x^{2} – 8x + k = 0 will both have real roots, is

(a) 4

(b) 8

(c) 12

(d) 16

**Solution:**

**(d)** In the equation x^{2} + kx + 64 = 0

**Question 7.**

**Solution:**

**(b)**

Which is not possible

x = 3 is correct

**Question 8.**

If 2 is a root of the equation x^{2} + bx + 12 = 0 and the equation x^{2} + bx + q = 0 has equal roots, then q =

(a) 8

(b) – 8

(c) 16

(d) -16

**Solution:**

**(c)**

**Question 9.**

If the equation (a^{2} + b^{2}) x^{2} – 2 (ac + bd) x + c^{2} + d^{2} = 0 has equal roots, then

(a) ab = cd

(b) ad = bc

(c) ad = √bc

(d) ab = √cd

**Solution:**

**(b)**

**Question 10.**

If the roots of the equation (a^{2} + b^{2}) x^{2} – 2b (a + c) x + (b^{2} + c^{2}) = 0 are equal, then ;

(a) 2b = a + c

(b) b^{2} = ac

(c) b =

(d) b = ac

**Solution:**

**(b)**

**Question 11.**

If the equation x^{2} – bx + 1 = 0 does not possess real roots, then

(a) -3 < b < 3

(b) -2 < b < 2

(c) b > 2

(d) b < -2

**Solution:**

**(b)**

**Question 12.**

If x = 1 is a common root of the equations ax^{2} + ax + 3 = 0 and x^{2} + x + b = 0, then ab =

(a) 3

(b) 3.5

(c) 6

(d) -3

**Solution:**

**(a)** In the equation

ax^{2} + ax + 3 = 0 and x^{2} + x + b = 0

Substituting the value of x = 1, then in ax^{2} + ax + 3 = 0

**Question 13.**

If p and q are the roots of the equation x^{2} – px + q + 0, then

(a) p = 1, q = -2

(b) p = 0, q = 1

(c) p = -2, q = 0

(d) p = -2, q = 1

**Solution:**

**(a)**

**Question 14.**

If a and b can take values 1, 2, 3, 4. Then the number of the equations of the form ax^{2} + bx + 1 = 0 having real roots is

(a) 10

(b) 7

(c) 6

(d) 12

**Solution:**

**(b)**

ax^{2} + bx + 1 = 0

D = b^{2} – 4a = b^{2} – 4a

Roots are real

D ≥ 0

=> b^{2} – 4a ≥ 0

=> b^{2} ≥ 4a

Here value of b can be 2, 3 or 4

If b = 2, then a can be 1,

If b = 3, then a can be 1, 2

If b = 4, then a can be 1, 2, 3, 4

No. of equation can be 7

**Question 15.**

The number of quadratic equations having real roots and which do not change by squaring their roots is

(a) 4

(b) 3

(c) 2

(d) 1

**Solution:**

**(c)** There can be two such quad, equations whose roots can be 1 and 0

The square of 1 and 0 remains same

No. of quad equation are 2

**Question 16.**

If (a^{2} + b^{2}) x^{2} + 2(ab + bd) x + c^{2} + d^{2} = 0 has no real roots, then

(a) ad = bc

(b) ab = cd

(c) ac = bd

(d) ad ≠ bc

**Solution:**

**(d)**

**Question 17.**

If the sum of the roots of the equation x^{2} – x = λ (2x – 1) is zero, then λ =

(a) -2

(b) 2

(c) –

(d)

**Solution:**

**(c)**

**Question 18.**

If x = 1 is a common root of ax^{2} + ax + 2 = 0 and x^{2} + x + b = 0 then, ab =

(a) 1

(b) 2

(c) 4

(d) 3

**Solution:**

**(b)**

**Question 19.**

The value of c for which the equation ax^{2} + 2bx + c = 0 has equal roots is

**Solution:**

**(a)**

**Question 20.**

If x^{2} + k (4x + k – 1) + 2 = 0 has equal roots, then k =

**Solution:**

**(b)**

**Question 21.**

If the sum and product of the roots of the equation kx^{2} + 6x + 4k = 0 are equal, then k =

**Solution:**

**(b)**

**Question 22.**

If sin α and cos α are the roots of the equations ax^{2} + bx + c = 0, then b^{2} =

(a) a^{2} – 2ac

(b) a^{2} + 2ac

(b) a^{2} – ac

(d) a^{2} + ac

**Solution:**

**(b)**

**Question 23.**

If 2 is a root of the equation x^{2} + ax + 12 = 0 and the quadratic equation x^{2} + ax + q = 0 has equal roots, then q =

(a) 12

(b) 8

(c) 20

(d) 16

**Solution:**

**(d)**

**Question 24.**

If the sum of the roots of the equation x^{2} – (k + 6) x + 2 (2k – 1) = 0 is equal to half of their product, then k =

(a) 6

(b) 7

(c) 1

(d) 5

**Solution:**

**(b)** In the quadratic equation

x^{2} – (k + 6) x + 2 (2k – 1) = 0

Here a = 1, b = – (k + 6), c = 2 (2k – 1)

**Question 25.**

If a and b are roots of the equation x^{2} + ax + b = 0, then a + b =

(a) 1

(b) 2

(c) -2

(d) -1

**Solution:**

**(d)** a and b are the roots of the equation x^{2} + ax + b = 0

Sum of roots = – a and product of roots = b

Now a + b = – a

and ab = b => a = 1 ….(i)

2a + b = 0

=> 2 x 1 + b = 0

=> b = -2

Now a + b = 1 – 2 = -1

**Question 26.**

A quadratic equation whose one root is 2 and the sum of whose roots is zero, is

(a) x^{2} + 4 = 0

(b) x^{2} – 4 = 0

(c) 4x^{2} – 1 = 0

(d) x^{2} – 2 = 0

**Solution:**

**(b)** Sum of roots of a quad, equation = 0

One root = 2

Second root = 0 – 2 = – 2

and product of roots = 2 x (-2) = – 4

Equation will be

x^{2} + (sum of roots) x + product of roots = 0

x^{2} + 0x + (-4) = 0

=> x^{2} – 4 = 0

**Question 27.**

If one root of the equation ax^{2} + bx + c = 0 is three times the other, then b^{2} : ac =

(a) 3 : 1

(b) 3 : 16

(c) 16 : 3

(d) 16 : 1

**Solution:**

**(c)**

**Question 28.**

If one root of the equation 2x^{2} + kx + 4 = 0 is 2, then the other root is

(a) 6

(b) -6

(c) -1

(d) 1

**Solution:**

**(d)** The given quadratic equation 2x^{2} + kx + 4 = 0

One root is 2

Product of roots = = = 2

Second root = = 1

**Question 29.**

If one root of the equation x^{2} + ax + 3 = 0 is 1, then its other root is

(a) 3

(b) -3

(c) 2

(d) -2

**Solution:**

**(a)** The quad, equation is x^{2} + ax + 3 = 0

One root =1

and product of roots = = = 3

Second root = = 3

**Question 30.**

If one root of the equation 4x^{2} – 2x + (λ – 4) = 0 be the reciprocal of the other, then λ =

(a) 8

(b) -8

(c) 4

(d) -4

**Solution:**

**(a)**

**Question 31.**

If y = 1 is a common root of the equations ay^{2} + ay + 3 = 0 and y^{2} + y + b = 0, then ab equals

(a) 3

(b) –

(c) 6

(d) -3 **[CBSE 2012]**

**Solution:**

**(a)**

**Question 32.**

The values of k for which the quadratic equation 16x^{2} + 4kx + 9 = 0 has real and equal roots are

(a) 6, –

(b) 36, -36

(c) 6, -6

(d) , – **[CBSE 2014]**

**Solution:**

**(c)** 16x^{2} + 4kx + 9 = 0

Here a = 16, b = 4k, c = 9

Now D = b^{2} – 4ac = (4k)^{2} – 4 x 16 x 9 = 16k^{2} – 576

Roots are real and equal

D = 0 or b^{2} – 4ac = 0

=> 16k^{2} – 576 = 0

=> k^{2} – 36 = 0

=> k^{2} = 36 = (± 6)^{2}

k = ± 6

k = 6, -6

Hope given RD Sharma Class 10 Solutions Chapter 4 Quadratic Equations MCQS are helpful to complete your math homework.

If you have any doubts, please comment below. Learn Insta try to provide online math tutoring for you.

Aditya pandey says

nyc